Transformation of the medical care system in Kazakhstan: the role and potential of specialists with extended medical practice. (Bangladesh Journal of Medical Science, 2026)
Background Kazakhstan’s healthcare system faces significant challenges, including limited access to care in rural areas and a shortage of healthcare professionals. Advanced Practice Nurses (APNs), with their advanced education and clinical expertise, have been shown to improve healthcare access and quality worldwide, especially in underserved regions. Despite this potential, the role of APNs in Kazakhstan is underdeveloped. Aim This study aims to explore the perceptions, challenges, and opportunities surrounding the integration of APNs into Kazakhstan’s healthcare system. It examines the barriers to adopting APN roles and investigates the potential impact of APNs on improving healthcare delivery, particularly in rural areas. Methods A qualitative design was used, involving semi-structured interviews with 15 participants, including nurses, healthcare administrators, and policymakers. Data were analyzed thematically to identify key barriers, perceptions, and opportunities related to the integration of APNs into the healthcare system. Findings will inform policy and provide recommendations for APN development in Kazakhstan. Results The study found a lack of awareness about APN roles, particularly in rural areas, with regulatory and educational barriers hindering their integration. Resistance from physicians and the absence of graduatelevel nursing programs were key challenges. However, participants recognized the potential of APNs to improve healthcare access and outcomes, especially in underserved areas. Conclusion To successfully integrate APNs into Kazakhstan’s healthcare system, clear regulatory frameworks, advanced nursing education, and stronger interprofessional collaboration are essential. These steps will help improve healthcare access and outcomes, particularly in rural areas.BJMS, Vol. 25 No. 01 January’26 Page : 317-326